The Making of Gender Equality in Tunisia and Implications for Development - Baliamoune, Mina (Washington, DC: World Bank, 2012)
In 1965, Tunisia's real GDP per capita was 645 Tunisian dinars (TD). Twenty years later, it rose to TD 1,285 (about double its level in 1965). In 2005, Tunisia increased its per capita real GDP to TD 2,480. While this may seem to be a substantial increase in income over four decades, it pales compared to Tunisia's achievements in other aspects of human development, particularly in education, health and gender equality. Indeed, Tunisia's achievements in these areas are remarkable. Baliamoune-Lutz undertook an analysis of Tunisia's path to development and concluded that "Tunisia's development strategy has relied primarily on diversifying its production, expanding the trade sector (both in terms of the size of its share and in terms of trade diversification), and human development--with a special emphasis on gender equality" (Baliamoune-Lutz, 2009a, p. 15). The empowerment of women, in particular, seems to have contributed significantly to raising the level of human development in the country.